PERLINDUNGAN HAK MASYARAKAT TERHADAP PRAKTIK LAND GRABBING DI INDONESIA: ANALISIS HUKUM AGRARIA DAN HUKUM ISLAM - A. Rahman La Onu (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2026)
The practice of land grabbing in Indonesia has increased alongside the expansion of investment, infrastructure development, plantations, and mining activities, which may reduce communities' access to land as a primary source of livelihood. This study aims to analyze the protection of community rights against land grabbing from the perspectives of agrarian law and Islamic law and to formulate an integrative legal protection model. This research employs a normative legal method using statutory, conceptual, and comparative approaches through library research. The findings indicate that national agrarian law and Islamic law share common principles by emphasizing justice, public welfare, and the protection of rights in agrarian resource management. Strengthening agrarian reform, recognizing indigenous communities, improving land governance transparency, enhancing public participation, and enforcing the law are essential measures to prevent land grabbing. The integration of these two legal systems is expected to create a fair and sustainable land management system.